FAMILY INVOLVEMENT IN ECOLOGICAL DA’WAH THROUGH “SAIPUL BIMBANG” - Patmawati Patmawati; Santa Rusmalita; Wardah Wardah (Raheema, 2019)
Garbage is a classic problem in our environment, including in Banjar Serasan. The society live on the Kapuas river banks and usually throw the garbage in the river, as the river were a large garbage can that will carry their trash at low tide. They also used the river for bathing and washing, which in turn will also affect their health. This is what makes environmentalists from the village, health center, and maternal and child health services conducted ecological da’wah through “Saipul Bimbang”. It stands for "Garbage Collected Bring Weighing". The activities involved families, especially mothers who will weigh their babies while carrying a bag of trash. This research was a qualitative. The data obtained through observation, interviews and documentation. The results showed that the family played an important role in ecological da’wah through “Saipul Bimbang”. The method used was face to face, counseling and activities involving mothers and babies. The result of this ecological da’wah is the increase of society’s awareness that garbage is not an environmental disturbance, even garbage is a blessing, as long as garbage can be processed and utilized. Keywords: Ecological Da’wah, Garbage, Blessing, Saipul Bimbang Sampah adalah masalah klasik di lingkungan kita, termasuk di Banjar Serasan. Masyarakat tinggal di tepi sungai Kapuas dan biasanya membuang sampah di sungai, karena sungai itu adalah tong sampah besar yang akan membawa sampah mereka pada saat air surut. Mereka juga menggunakan sungai untuk mandi dan mencuci, yang pada gilirannya juga akan mempengaruhi kesehatan mereka. Inilah yang membuat para pencinta lingkungan dari desa, pusat kesehatan, dan layanan kesehatan ibu dan anak melakukan dakwah ekologi melalui “Saipul Bimbang”. Singkatan dari "Garbage Collected Bring Weighing". Kegiatan tersebut melibatkan keluarga, terutama para ibu yang akan menimbang bayi mereka sambil membawa kantong sampah. Penelitian ini adalah kualitatif. Data diperoleh melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa keluarga memainkan peran penting dalam dakwah ekologi melalui “Saipul Bimbang”. Metode yang digunakan adalah tatap muka, konseling dan kegiatan yang melibatkan ibu dan bayi. Hasil dakwah ekologis ini adalah meningkatnya kesadaran masyarakat bahwa sampah bukanlah gangguan lingkungan, bahkan sampah adalah berkah, selama sampah dapat diolah dan dimanfaatkan. Keywords: Da’wah Ekologi, Sampah, Sukarela, Saipul Bimbang